Work Related Quality of Life among Medical Technologists in Regional Hospital, Ministry of Public Health - เปียถนอม, อาทิตยา; สัตยสมบูรณ์, ยุวนุช (Journal of Health Science of Thailand, 2022)
A high quality of work life is essential for organizations to continue to attract and retain employees. This cross-sectional explanatory study aimed to assess work related quality of life (WQL) among the medical technologist in regional hospital, Ministry of Public Health. A sample of 250 medical technologists who had worked at least 6 months were selected. Data were collected during December 2016 to December 2017 using a self-administered questionnaire which was reliable (a>0.7). Descriptive statistics were used to explain the variables. Pearson’s product moment correlation and stepwise multiple regression analysis were used to identify associated factors and predictors. The results showed that WQL among medical technologists in regional hospital and organization climate were at a high level (mean= 3.65±0.64, and 3.49±0.39, respectively). Job characteristics were at a medium level (mean=3.77±0.51). The job characteristics and organization climate were positively associated with WQL (r=0.346 and 0.734, respectively, p<0.05) and they were the predictors in regression model that jointly explained 54.1% of the variance in the WQL (adjusted R2 =0.541, p<0.05). To promote the quality of work life of this group of personnel, the study suggested supervisors support, help and solve problems in the job as well as create good relationships in the workplace.